2010
DOI: 10.1103/physrevlett.105.090604
|View full text |Cite
|
Sign up to set email alerts
|

Hot Brownian Motion

Abstract: We derive the markovian description for the nonequilibrium brownian motion of a heated nanoparticle in a simple solvent with a temperature-dependent viscosity. Our analytical results for the generalized fluctuation-dissipation and Stokes-Einstein relations compare favorably with measurements of laser-heated gold nanoparticles and provide a practical rational basis for emerging photothermal tracer and nanoparticle trapping and tracking techniques.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
200
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 188 publications
(211 citation statements)
references
References 30 publications
6
200
0
1
Order By: Relevance
“…Brownian motion in nonequilibrium systems is of particular interest because it is directly related to the transport of molecules and cells in biological systems. Important examples include Brownian motors [38,39], active Brownian motion of self-propelled particles [40][41][42][43][44][45][46], hot Brownian motion [47], and Brownian motion in shear flows [48]. Recent theoretical studies also found that the inertias of particles and surrounding fluids can significantly affect the Brownian motion in nonequilibrium systems [49][50][51][52][53][54].…”
Section: Introductionmentioning
confidence: 99%
“…Brownian motion in nonequilibrium systems is of particular interest because it is directly related to the transport of molecules and cells in biological systems. Important examples include Brownian motors [38,39], active Brownian motion of self-propelled particles [40][41][42][43][44][45][46], hot Brownian motion [47], and Brownian motion in shear flows [48]. Recent theoretical studies also found that the inertias of particles and surrounding fluids can significantly affect the Brownian motion in nonequilibrium systems [49][50][51][52][53][54].…”
Section: Introductionmentioning
confidence: 99%
“…[5]. More recently, the Brownian motion of a small heated sphere, a so-called hot particle, has been investigated [6,7]. The authors discovered that the particle diffusion has distinct features from the case of diffusion in isothermal systems.…”
Section: Introductionmentioning
confidence: 99%
“…To model experiments on the motion of a heated particle [7], the continuous spatial variation of viscosity was approximated by Chakraborty et al [6] using a set of spherical shells of monotonically changing but constant viscosity. Since the solution to the constant viscosity problem is straightforward, multiple such solutions can be stitched together.…”
Section: Introductionmentioning
confidence: 99%
“…The optical forces acting on the particle are calculated using generalized Mie theory [23]. The temperature increase in the surroundings of the particle is calculated by determining the absorption of the laser light by the iron oxide inclusions [25] and by using the stationary heat equation to estimate the ensuing heat conduction [26]. This temperature increase causes a local demixing of the binary solution near the particle resulting in an increase in the local concentration of water, because of the hydrophilicity of the particle's surface.…”
Section: Numerical Simulationsmentioning
confidence: 99%